Siegius, a replacement name for Bilobatus Sieg, 1993 (Crustacea: Tanaidacea: Apseudidae), preoccupied by Bilobatus Machatschke, 1970 (Insecta: Coleoptera: Scarabaeidae: Rutelinae) - Allsopp, Peter G. (Zootaxa, 2017)
Sieg (1993) established the then monotypic genus Bilobatus for his new species crenulatus, an apseudomorphan tanaidacean from Darwin Harbour, Northern Territory, Australia. The genus was later synonymised under Apseudes Leach, 1814 by Bamber (2000), but then revalidated by Guţu (2002); it is currently considered valid (Blazewicz-Paszkowycz1 et al. 2012; Anderson 2016).